Using a high-frequency carrier does not improve comfort of transcutaneous spinal cord stimulation. (1st February 2023) - Dalrymple, Ashley N; Hooper, Charli Ann; Kuriakose, Minna G; Capogrosso, Marco; Weber, Douglas J
Abstract: Objective. Spinal cord neuromodulation has gained much attention for demonstrating improved motor recovery in people with spinal cord injury, motivating the development of clinically applicable technologies. Among them, transcutaneous spinal cord stimulation (tSCS) is attractive because of its non-invasive profile. Many tSCS studies employ a high-frequency (10 kHz) carrier, which has been reported to reduce stimulation discomfort. However, these claims have come under scrutiny in recent years. The purpose of this study was to determine whether using a high-frequency carrier for tSCS is more comfortable at therapeutic amplitudes, which evoke posterior root-muscle (PRM) reflexes. Approach. In 16 neurologically intact participants, tSCS was delivered using a 1 ms long monophasic pulse with and without a high-frequency carrier. Stimulation amplitude and pulse duration were varied and PRM reflexes were recorded from the soleus, gastrocnemius, and tibialis anterior muscles. Participants rated their discomfort during stimulation from 0 to 10 at PRM reflex threshold. Main Results. At PRM reflex threshold, the addition of a high-frequency carrier (0.87 ± 0.2) was equally comfortable as conventional stimulation (1.03 ± 0.18) but required approximately double the charge to evoke the PRM reflex (conventional: 32.4 ± 9.2 µ C; high-frequency carrier: 62.5 ± 11.1 µ C). Strength-duration curves for tSCS with a high-frequency carrier had a rheobase that was 4.8× greater and a chronaxie that was 5.7× narrower than the conventional monophasic pulse, indicating that the addition of a high-frequency carrier makes stimulation less efficient in recruiting neural activity in spinal roots. Significance. Using a high-frequency carrier for tSCS is equally as comfortable and less efficient as conventional stimulation at amplitudes required to stimulate spinal dorsal roots.